2016
DOI: 10.1103/physreve.93.010401
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium microphase separation in the two-leaflet model of lipid membranes

Abstract: Because of the coupling between local lipid composition and the thickness of the membrane, microphase separation in two-component lipid membranes can take place; such effects may underlie the formation of equilibrium nanoscale rafts. Using a kinetic description, this phenomenon is analytically and numerically investigated. The phase diagram is constructed through the stability analysis for linearized kinetic equations, and conditions for microphase separation are discussed. Simulations of the full kinetic mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…-In general, phase separation in binary liquid mixtures completes by relaxation below the transition temperature. However, it is also well known that the competition between local attractive and long-ranged repulsive interactions between two phases leads to stable micro-phase separation [1][2][3][4][5][6][7]. The coarsening dynamics from a homogeneous phase to macro-or micro-phase has been extensively investigated in binary mixture systems of polymeric and/or low-molecular-weight molecules [3,4,8].…”
mentioning
confidence: 99%
“…-In general, phase separation in binary liquid mixtures completes by relaxation below the transition temperature. However, it is also well known that the competition between local attractive and long-ranged repulsive interactions between two phases leads to stable micro-phase separation [1][2][3][4][5][6][7]. The coarsening dynamics from a homogeneous phase to macro-or micro-phase has been extensively investigated in binary mixture systems of polymeric and/or low-molecular-weight molecules [3,4,8].…”
mentioning
confidence: 99%
“…Reigada and Mikhailov [164] have recently carried out a linear stability analysis and dynamic Ginzburg-Landau simulations of a monolayer curvature coupling model and calculated a phase diagram in a different plane of parameters than Fig. 8.…”
Section: Monolayer Curvature Couplingmentioning
confidence: 99%
“…It has been suggested that equilibrium nanoscale rafts can result from micro-phase separation effects that are observed when interactions between the two layers in a membrane are taken into account (see, e.g., Refs. [11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%